The Prosperity Index and Its Relationship with Economic Growth: Case of Turkey - Büyüksarıkulak, Ahmet Mesut; Kahramanoğlu, Ali (Journal of Entrepreneurship, Business and Economics; Vol 7 No 2 (2019), 2019)
Economic growth has been one of the most important subjects of economics in almost every period. It can be said that first, economic growth, then the increment of the prosperity levels of countries is aimed with economic policies. For measuring welfare; In addition to income method, new parameters such as education, health, environment and management were included in the calculation The objective of this study is to evaluate The Legatum Prosperity Index results, prepared by The Legatum Institute as an alternative approach to measure prosperity, between 2007-2017 with regards to Turkey and to associate these with economic growth. In the creation of the index, economic quality, business environment, health, education, security, natural environment, management, personal liberties, social capital criteria are used. In the last decade, Turkey’s economy experienced a recession only in 2009 but grew in other years. When we examine the ranking on the Prosperity Index, it is observed that it has generally a horizontal course. This situation indicates that economic growth has not contributed to prosperity increase enough in Turkey. It can be interpreted as Turkey’s prosperity level will not progress significantly in the coming years, considering the constant retrogressing in rankings especially in the last three years. Research paper Keywords: Economic Growth; Turkey; Prosperity Index; Welfare; Measurement of Welfare Reference to this paper should be made as follows: Büyüksarıkulak, A. M. & Kahramanoğlu, A. (2019). The Prosperity Index and Its Relationship with Economic Growth: Case of Turkey, Journal of Entrepreneurship, Business and Economics , 7 (2), 1–30.